Los espacios "del miedo", ciudad y género. Experiencias y percepciones en Zaragoza - Añover López, María (Geographicalia, 2014)
The fear is deeply related to race, class, age and especially with the genre. From this view, the female gender in social life can not be explained without the exclusion of this at the time of building the city. Urban characteristics such as poor lighting, access to housing, parks, tickets..., these factors related to the existence of people in the street, whether it is day or night, the security image transmitted by means of communication toughest neighborhoods and streets due to the presence of subjects perceived as dangerous..., make the city not for women. So, my object of study is aimed at unraveling the specifications of urban fear Zaragoza studying two districts with very different characteristicsof habitability through the different perceptions of individuals living in each area, all from a gender perspective.